KARAKTERISTIK PETANI TANAMAN PERKEBUNAN DAN KONSTRIBUSI TERHADAP PENDAPATAN RUMAHTANGGA DI KECAMATAN NUSANIWE KOTA AMBON - August Ernst Pattiselanno; Edizon Jambormias; Junianita Fridianova Sopamena (Agric, 2018)
Ambon as the capital of Maluku Province had been occupied by 3,558 farmers whose farming works have contributed to the production of estate commodities for about 1,169 tons. There were three estate commodities with significant contribution, namely clove, nutmeg, and coconut. The objective of research was to analyze the characteristics of estate farmers and the contribution of estate commodities on household income. Sample was determined purposively from Nusaniwe District, precisely 30 farmers from Nusaniwe Subdistrict, 60 farmers from Latuhalat Subdistrict, 50 farmers from Amahusu Subdistrict, and 60 farmers from Urimessing Subdistrict. Total sample was 200 farmers. Data were collected using questionnaire and depth interview with key informant. Data on respondent characteristic were analyzed through simple tabulation. Income count was used to analyze the contribution of each estate commodity on household income. Result of research showed that education, number of household member, side-job selection, land width, and commodity species were not varying across subdistricts. Contribution of clove and nutmeg to household income was found as high for 70 – 80 %, while that of coconut reached only 10 – 20%. Side-job activity as fisher and construction worker gave contribution to household income for 5 – 10%.